Assessing the predictive power of immune microenvironment-related genes and clinical immune-inflammatory parameters in breast cancer - Shangyi Lu; Shun Liang; Fucai Chen; Jianyuan Meng; Junwei Chen; Yi Lu; Gangjian Zhu (All Life)
This study aims to improve breast cancer (BC) prognostic biomarker detection, overcoming current methods’ complexity, high – cost, and low – precision issues. 152 Breast Invasive Carcinoma (BRCA) samples from TCGA were analyzed using the Estimate algorithm, identifying 256 down – regulated and 239 up – regulated Differentially Expressed Genes (DEGs) related to immune and inflammatory pathways. Through MCC algorithm and survival analysis, 10 prognosis – linked genes were found. Clinical immune – inflammatory markers like NLR, LMR, PLR, and SII correlated with 5 – year disease-free survival (DFS) in BC patients. A cohort of 60 BC patients was clinically validated. High expression of CD3E, CD40LG, CD3D, and IL2, and CD79A – negative expression were associated with longer DFS and overall survival (OS). Higher NLR, PLR, and SII meant shorter survival, while higher LMR was better. These results offer potential biomarkers for personalized prognosis and new ideas for targeted therapies.